Vertical two-dimensional layered fused aromatic ladder structure - Noh, Hyuk-Jun (Nat Commun, 2020)
Planar two-dimensional (2D) layered materials such as graphene, metal-organic frameworks, and covalent-organic frameworks are attracting enormous interest in the scientific community because of their unique properties and potential applications. One common feature of these materials is that their building blocks (monomers) are flat and lie in planar 2D structures, with interlayer π–π stacking, parallel to the stacking direction. Due to layer-to-layer confinement, their segmental motion is very restricted, which affects their sorption/desorption kinetics when used as sorbent materials. Here, to minimize this confinement, a vertical 2D layered material was designed and synthesized, with a robust fused aromatic ladder (FAL) structure. Because of its unique structural nature, the vertical 2D layered FAL structure has excellent gas uptake performance under both low and high pressures, and also a high iodine (I(2)) uptake capacity with unusually fast kinetics, the fastest among reported porous organic materials to date.